SOSIALISASI DENGAN TEMA ANALISIS TINGKAT KESADARAN DAN FAKTOR RISIKO DIABETES MELITUS PADA MASYARAKAT DESA SUKAMARGA MELALUI SKRINING GULA DARAH: UPAYA PREVENTIF BERBASIS KOMUNIKASI DAN ASPEK HUKUM KESEHATAN - Hifni, Mohammad; Abelia,; Tiara Kurniati,; Adhitya, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This outreach program aims to analyze the level of awareness and identify risk factors for Diabetes Mellitus (DM) in the Sukamarga Village community through blood sugar screening as a preventive measure. The outreach program was implemented using an interactive health communication approach and based on health law education to increase public understanding of their rights and obligations in disease prevention. The methods used included counseling, blood sugar level checks, and participatory discussions on healthy lifestyles and relevant health regulations. The results of the activity showed that most participants had a low level of awareness of the risks of DM, with the dominant risk factors being an unbalanced diet and lack of physical activity. Through this activity, the community gained knowledge about the importance of early detection, implementing a healthy lifestyle, and understanding the legal aspects related to health services. This outreach program is expected to be a strategic step in reducing the prevalence of DM in the village area through preventive efforts and sustainable community empowerment.